Conventional Switching to Drive A Brush DC Geared Servomotor. Issue 1 (June 2021) - Syafruddin, R; Anung,; Muntiyono,; Lestari, Ninik Sri; Afiyah, Salamatul; Hidayat, Rahmad; Mahardika, Andrew Ghea
Abstract: Conventional switching can be used to drive a brush dc geared servomotor, in terms of adjusting the position to our liking. For brush geared dc servomotor drivers we use a switching bridge where each arm is used a power transistor, in the process of switching bridge need to be considered the area where the short circuit is likely to occur, to avoid it we use dead time, as well as the possibility of a short circuit due to the upper arm and the lower arm of the bridge turns on at the same time for that it is necessary to make a transistor-transistor logic circuit so that the upper arm will not turn on when the lower arm is on or vice versa. From the results of conventional switching, it is able to drive the DC brush geared servomotor to the desired position.